Transforming Afghanistan: Enhancing Technology Access to Overcome Gender Discrimination - Nabizada, Shamsiya; Quraishi, Tamanna; Sadat, Roqia; Kirmani, Atifa; Hashemi, Zainab; Haidari, Nooria; Faramarz, Nilufar (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
Gender disparity in technology access and empowerment remains a significant challenge in Afghanistan, particularly for women facing socio-cultural barriers. This study explores the perceptions of Afghan women regarding technology access and empowerment at Kabul University. Despite advancements in technology, Afghan women encounter obstacles in accessing and utilizing technological resources, limiting their opportunities for education, employment, and economic empowerment. This research aims to investigate the perceptions of Afghan women regarding technology access and empowerment, with a focus on identifying barriers and opportunities for improvement. A cross-sectional study was conducted at Kabul University, involving 150 participants from diverse fields of education/employment and age groups. Structured surveys were administered electronically to collect data on participants' perceptions of technology access and empowerment. Descriptive statistics were used to analyze the data. The analysis revealed diverse perceptions among Afghan women regarding technology access and empowerment, with significant disparities in infrastructure accessibility and the effectiveness of digital literacy programs. The findings highlight the need for targeted interventions to address barriers and enhance technology access and empowerment for Afghan women, ultimately promoting gender equity and socio-economic development.